2009
DOI: 10.1063/1.3115767
|View full text |Cite
|
Sign up to set email alerts
|

Origin of low threshold field emission from nitrogen-incorporated nanocrystalline diamond films

Abstract: Highly conductive, nitrogen-incorporated nanocrystalline diamond films with quasimetallic character emit electrons at low turn-on fields (∼3 V μm−1). These films exhibit stronger delocalization of carriers, indicative of smaller energy separation between the defect bands in the band gap. We show that the emission level derived from the measured emission characteristic and electron affinity shifts upward (up to a few eV) with increasing the film conductivity, thereby decreasing the effective potential barrier h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…, were therefore employed to characterize the atomic bonding and surface morphology of nitrogen‐doped conductive UNCD films before and after the ECTs. In the Raman spectra, the position and relative intensity of five Raman peaks, corresponding to trans‐polyacetylene (1141 and ∼1480 cm −1 ), D and G peaks of sp 2 ‐bonded carbon (1353 and 1547 cm −1 ) and sp 3 ‐bonded carbon (1332 cm −1 ), respectively , have no obvious change before and after the ECTs. By carefully comparing the SEM images in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, were therefore employed to characterize the atomic bonding and surface morphology of nitrogen‐doped conductive UNCD films before and after the ECTs. In the Raman spectra, the position and relative intensity of five Raman peaks, corresponding to trans‐polyacetylene (1141 and ∼1480 cm −1 ), D and G peaks of sp 2 ‐bonded carbon (1353 and 1547 cm −1 ) and sp 3 ‐bonded carbon (1332 cm −1 ), respectively , have no obvious change before and after the ECTs. By carefully comparing the SEM images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the electrical conductivity of nitrogen‐doped UNCD films rapidly increases and tends to be saturated at about 100 Ω −1 cm −1 . The good conductivity of nitrogen‐doped UNCD films originates from the increasing sp 2 ‐bonded carbon in the grain boundaries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we include only d.b., p, and p* states for simplification based on a simulation study. 5 The Fermi level position and the electron affinity for the NCD are based on our measurement by ultraviolet photoelectron spectroscopy, 18 while those for Si are taken from Ref. 15.…”
Section: Carrier Transport Mechanism In Ncd/si Heterojunctionsmentioning
confidence: 99%
“…In order to improve the FE characteristics of thin film cathodes, lots of methods have been proposed, e.g., the advanced materials [2] with low and even negative electron affinity or post-treatment [3] to reduce effective work function or improve field enhancement factor. On the other hand, it was found that quantum well states in two-layer ultrathin film cathodes can be considerably improve the FE properties [4], and the FE properties can be evidently affected by the potential well/barrier structure [5], which suggests an simple method to improve the FE characteristic by construct a quantum potential well/barrier structure and modulating the quantum structure of the thin films.…”
Section: Introductionmentioning
confidence: 99%